U.S. Mass Media, American Public Opinion and the Kosovo War: Insinuating Belligerence or Soothing Political Tension? - Benzid, Selma; Aboubou, Hachemi (المجلة الجزائرية للأمن الإنساني, 2023)
The atrocities committed by the Serbian president Slobodan Milošević’s regime during the Kosovo war in the late 1990s prompted the U.S. to launch a NATO humanitarian intervention there even without the U.N. approval. That mission was coined the name Operation Allied Force. The U.S. mass media was, like it has constantly been, present during all the phases of this crisis. As it is claimed, news coverage has always something to do with shaping the American public opinion on foreign affairs and thus the politicians’ decision making might be influenced too. Therefore, this paper primarily focuses on one side of the communication process which is concerned with the American audience’s interpretation of that conflict’s news. Additionally, this piece of research tends to study this mutually entangled influence to ultimately reach a conclusion on whether the American mass media was insinuating belligerence or tending to sooth the political tension during the Balkan crisis. In this process, the descriptive and the historical methods are used through reviewing previous relevant field research, articles and studies that dealt with the American mass media’s coverage of the Kosovo war and its impact on both the U.S. public and political policymakers.